Therapeutic Assessment of Vulvar Squamous Intraepithelial Lesions with CO2 Laser Vaporization in Immunosuppressed Patients - Julisa Chamorro Lascasas Ribalta; Mariana Vendramin Mateussi; Neila Maria de Góis Speck (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective A vulvar squamous intraepithelial lesion is deemed to be a preceding lesion to vulvar cancer, especially in women aged under 40 years, holders of an acquired or idiopathic immunosuppression. Several treatments have been used to treat these lesions. One of the aesthetically acceptable therapeutic methods is the CO2 laser vaporization. Methods In a transversal study, 46 records of immunosuppressed women bearing a vulvar low grade and/or high grade squamous intraepithelial lesion were selected out of the retrospective analysis, computing age, date of record, date of vulvar lesion treatment with CO2 laser, the time elapsed between the first and the last visit (in months), the number of visits, the presence or absence of condylomatous lesions in other female lower genital tract sites and whether or not recurrences and persistence of intraepithelial lesions have been noticed during the follow-up. Results Patients bearing vulvar high-grade squamous intraepithelial lesion and immunosuppressed (serumpositive forhumanimmunodeficiency virus [HIV] or with solid organs transplantation) have shown a higher level of persistence of lesions and a higher chance of having other areas of the female lower genital tract involved. Conclusion While the CO2 laser vaporization is the most conservative method for the treatment of vulvar high-grade intraepithelial lesions, it is far frombeing the ideal method, dueto the intrinsic infection features considered. The possibility of persistence, recurrences and spontaneous limited regression indicates that a closer surveillance in the long-term treated cases should be considered, in special for immunosuppressed patients.